P2P Lending: Legal Framework for Electronic Contracts - Hatta, M.; Susanto, Anthon F.; Narsudin, Udin (International Journal of Latin Notary, 2025)
This study examines Peer-to-Peer (P2P) Lending, a form of financial technology (Fintech) that directly connects lenders and borrowers through digital platforms, eliminating the traditional role of banking intermediaries. The research aims to address two key legal questions: How do electronic contracts protect the parties, and how does the electronic contract become valid and binding in P2P lending? This study employs a combination of literature review and fieldwork, utilizing secondary and primary data collected through document analysis and interviews. The data were analyzed using a juridical-qualitative method. The findings show that conventional civil law generally regulates contracts, but does not explicitly address the nature and enforcement of electronic contracts. Legal protection in digital loan agreements is established through the principles of digital governance, particularly regarding the rights, obligations, and liabilities of the parties. An electronic contract is considered valid when the essential elements of a contract are fulfilled and supported by a verifiable electronic signature, under widely accepted legal and technological standards. The study concludes that while existing contract law provides a general foundation, digital transactions require adaptive legal interpretations to ensure enforceability, accountability, and user protection in the evolving digital financial ecosystem.